2021
DOI: 10.3389/fmicb.2021.770370
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Labrenzia aggregata (Alphaproteobacteria) Strains Isolated From the Mariana Trench: Insights Into the Metabolic Potentials and Biogeochemical Functions

Abstract: Hadal zones are marine environments deeper than 6,000 m, most of which comprise oceanic trenches. Microbes thriving at such depth experience high hydrostatic pressure and low temperature. The genomic potentials of these microbes to such extreme environments are largely unknown. Here, we compare five complete genomes of bacterial strains belonging to Labrenzia aggregata (Alphaproteobacteria), including four from the Mariana Trench at depths up to 9,600 m and one reference from surface seawater of the East China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 73 publications
(90 reference statements)
0
12
0
Order By: Relevance
“…Previous studies have shown that the DMSP in coral holobionts is produced by both coral and Symbiodiniaceae (Raina et al 2013 ). The bacteria detected in corals, such as L. aggregate , might be able to degrade the generated DMSP into the climate-active gas DMS via the bacterial cleavage pathway (Zhong et al 2021 ). Prosthecochloris (photoautotrophic bacteria) participates in sulfur metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the DMSP in coral holobionts is produced by both coral and Symbiodiniaceae (Raina et al 2013 ). The bacteria detected in corals, such as L. aggregate , might be able to degrade the generated DMSP into the climate-active gas DMS via the bacterial cleavage pathway (Zhong et al 2021 ). Prosthecochloris (photoautotrophic bacteria) participates in sulfur metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A single colony was carefully selected and purified three times before strain identification (Zhao et al, 2020). The genome of the host strain was also obtained (accession number: CP045617) (Zhong et al, 2021).…”
Section: Culture Conditionsmentioning
confidence: 99%
“…Labrenzia aggregata, a member of order Hyphomicrobiales, class Alphaproteobacteria, is widespread in marine environments and actively contributes to nitrogen and sulfur cycles, playing roles in denitrification, dissimilatory nitrate reduction to ammonium (DNRA) (King, 2003;King and Weber, 2007), thiosulfate oxidation, as well as the biosynthesis and degradation of dimethylsulfoniopropionate (DMSP) (Curson et al, 2017). Recent studies revealed their presence in deep-sea environments, such as the Mariana Trench, due to their ability to survive and grow under high hydrostatic pressure conditions (Priyanka et al, 2014;Zhong et al, 2021). In addition, extensive horizontal gene transfer (HGT) events have been identified in L. aggregata genome, likely mediated by viruses (Zhong et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations